Shared leadership in interprofessional teams: beyond team characteristics to team conditions. Issue 4 (3rd July 2020) - Ong, Yu Han; Koh, Mervyn Yong Hwang; Lim, Wee Shiong
ABSTRACT: Shared leadership has been shown to enhance processes, effectiveness, and performances in interprofessional teams. While earlier studies suggest the association of internal team environment (ITE) and transactive memory system (TMS) with shared leadership, the relative influence of these team conditions vis-a-vis team characteristics (such as team size, stability, and interprofessional roles) on shared leadership is not well understood. This study aims to examine the comparative influence of team characteristics versus team conditions of ITE and TMS on shared leadership during interprofessional team meetings (IPTMs). We compared interprofessional teams from two departments, namely larger and more diverse teams of Geriatric Medicine versus the smaller and more homogeneous Palliative Medicine. We administered a questionnaire survey to healthcare professionals who attended IPTMs in both departments (N = 133). Our results revealed significantly higher scores in shared leadership, ITE and TMS in Palliative Medicine ( p < .05). Using hierarchical regression analysis adjusting for team conditions, department and number of IPTMs attended were not significant in the final model (both p > .05). Instead, TMS ( β = 0.250, p < .01) and ITE ( β = 0.584, p < .01) outperformed team characteristics as conditions that are highly associated with shared leadership, explaining an additional 29.8% and 19.0%, respectively, of model variance. Further analysis revealed a stronger correlation between shared leadership subdomains with TMS in Geriatric Medicine and with ITE in Palliative Medicine. Our results demonstrate how a positive working environment with a high level of shared memory engendered a perception of shared leadership, and how these team conditions can be tapped upon to circumvent differences in team characteristics to facilitate shared leadership. Identifying key conditions that are highly associated with shared leadership is critical for the teaching of dynamic leadership roles to junior clinicians which in turn, can enhance patient care.